Who will take care of them? A reflection on Southern European welfare regimes - Ciziceno, Marco (Society Register, 2024)
The age profile of a country influences the organization of healthcare arrangements for older people. In southern European countries, the low performance of the welfare state and traditional family-oriented culture have led to an informal and gendered model of care, with women often responsible for the (unpaid) caregiving work. However, the increasing female participation in the labour market challenges these welfare regimes, prompting a shift in family responsibilities outside the family. Moreover, in response to the growing need for long-term care workers, some European countries have relied on individuals with a “migratory background” rather than restructuring their public elderly care services. This article examines the demographic, cultural, economic, and social changes of southern welfare regimes. The introduction of policies that, directly or indirectly, eliminate gender stereotypes in informal caregiving work and the diffusion of equal family-care culture are measures that can no longer be postponed in addressing the future of such welfare regimes.